A new species of Trachylepis (Squamata: Scincidae) from the Amhara Region, Ethiopia, and a key to the Ethiopian Trachylepis - Koppetsch, Thore (Zootaxa, 2020)
Ethiopia is known for its highly endemic and rich herpetofaunal diversity shaped by its biogeographical patterns. Here, a new species of skink, Trachylepis boehmei sp. nov., is described from the Ethiopian Highlands. It differs from its congeners in having smooth uncarinated dorsal scales, 26–29 scale rows around midbody, a slender body of small size, a relatively short tail, a low eye–snout distance and a unique colour pattern with 6–8 darkish brown dorsal stripes. Based on morphological characteristics, its biogeographical pattern and comparisons with other similar congeners this new species is closely related to Trachylepis megalura. A published new record of Trachylepis wingati for the Kafa region is re-examined and identified as T. megalura. An updated comprehensive key to the Trachylepis found in Ethiopia is provided. In the context of ongoing phylogenetic and taxonomic revisions of Trachylepis and its species complexes the presence of further cryptic taxa can be expected also for the Ethiopian biodiversity hotspots. Consequently, the need of further herpetological investigations in this region of ecological importance is stressed.